Neale S. Godfrey's ultimate kids' money book - Godfrey, Neale S.; Verougstraete, Randy (New York : Simon & Schuster Books for Young Readers, 1998)
Provides an overview of economics and money, including earning, spending, saving, checks and credit cards, banks, and the history of money.
Includes index.
Wilson's Children.
Wilson's Junior High School.
School Library Journal starred.
5.3
3-6
Keywords: Finance -- Juvenile literature; Money -- Juvenile literature; Children -- Finance, Personal -- Juvenile literature; Saving and investment -- Juvenile literature; Money; Finance, Personal; Personal finance; Money; Saving and investment; Saving and investment; Money; Finance, Personal